ПАРАДИГМЫ УЧЕТА ЗАСТРАХОВАННЫХ ВОЗНАГРАЖДЕНИЙ РАБОТНИКАМ (Journal of Economic Research & Business Administration, 2015)
In conditions market economics rewarding employees subdivided in long-term and short- term. Analysis rewarding must promote to lowering out going member organizations. Other effective element of the mechanism of realization of scientific development in business is the principle of their compensation and introduced by them in manufacture